Early detection of anxiety symptoms in Autism Spectrum Disorder: An exploratory study in a Spanish sample of 3–6 year old children - Montserrat Durán-Bouza; Silvia Gómez-Ríos; Margarita Cañadas-Pérez; Juan-Carlos Brenlla-Blanco (PLoS ONE, 2025)
Current research often overlooks anxiety symptoms in preschoolers with Autism Spectrum Disorder (ASD), focusing on older children. This study examines anxiety symptomatology primarily in young children with ASD by analyzing data from 82 Spanish children aged 3- to 6 years. Parents completed the Anxiety Scale for Children with ASD and the Social Communication Questionnaire. Results indicate that 30.48% of the children exhibit significant anxiety symptoms, “with anxious uncertainty” being the most prevalent. Factor analysis reveals three principal components of the Anxiety Scale, supporting its reliability. Regression analysis highlights stereotypical behaviors as significant predictors of anxiety levels. These findings underscore the importance of early assessment and adaptation of assessment tools for preschoolers with ASD. Stereotypical behaviors are identified as key predictors of anxiety in this population.